Weight perception in overweight adolescents: Associations with body change intentions, diet and physical activity. (June 2015) - Fredrickson, Julia; Kremer, Peter; Swinburn, Boyd; de Silva, Andrea; McCabe, Marita
This study examined the association of weight perception and weight satisfaction with body change intentions and weight-related behaviours in 928 overweight adolescents (aged 11–18 years, 44% female). Accurate perception of weight was associated with trying to lose weight and inaccurate perception was associated with trying to gain muscle. Weight dissatisfaction was associated with trying to lose weight and gain muscle. Accurate weight perception and weight dissatisfaction were not associated with healthy weight-related behaviours. Awareness of overweight and body dissatisfaction may be detrimental to the adoption of healthy weight-control behaviours. Interventions with overweight adolescents should encourage body satisfaction, rather than promoting awareness of overweight.